The influence of organizational commitment and motivation on organizational citizenship behavior - Febriani, Asti; Aeni, Novita; Suzana, Anna (Institute of Computer Science (IOCS), 2025)
Organizational Citizenship Behavior refers to voluntary actions by employees that surpass their formal job duties, extending beyond role expectations and incentive-based performance. Such behaviors are anticipated to enhance overall workforce quality. The research focuses on understanding the relationships between these aspects and their contribution to OCB in workplace scenarios. This research method is quantitative by conducting surveys and interviews. In this study, the population is nurses with a total of 430 nurses. Data were analyzed using SEM-PLS, with 207 respondents sampled from Gunung Jati Hospital, Cirebon City